PEMBUATAN PROGAM APLIKASI INVENTORI DAN PENJUALAN PADA TOKO MITRA SAMBAS - Ailsa Bella; Tony Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Toko Mitra Sambas is located in Pontianak, West Kalimantan. Toko Mitra Sambas is a store that sells a variety of food and some grocery. Toko Mitra Sambas still using manual systems that make store have a some trouble for selling, purchase and inventory system. This has led many businesses to react quickly in adopting computerized system in promoting their business and compete with their competitors. Particularly through the application program that is increasingly widespread among the public.Therefore, if businesses do not adopt the computerized system, sooner or later they will have a huge disadvantage in terms of profitability and efficiency. Business, like a conventional store that specializes in food and furniture, also need a new computerized system to handle with daily activities, such as sales, orders, and purchases, so that data is added, search, edit, and delete it becomes easier and more efficient in terms of time and cost. This computerized applications intended to address the difficulties faced by the user system. If this system will be implemented in the future, hopefully useful for Toko Mitra Sambas.The steps of the manufacturing program includes: data collection, data analysis design method with a structured design method includes diagrams context diagram, ERD implementation and testing program. Applications designed using SQL Server 2012 and Visual Studio 2012. From the test results can take several conclusions, among which are: the application program can easily create reports accurately and sales transactions and inventory system regularly.